2017
DOI: 10.18632/oncotarget.15809
|View full text |Cite
|
Sign up to set email alerts
|

Lowered expression of microRNA-125a-5p in human hepatocellular carcinoma and up-regulation of its oncogenic targets sirtuin-7, matrix metalloproteinase-11, and c-Raf

Abstract: Human microRNA-125a-5p (miR-125a) is expressed in most tissues where it downregulates the expression of membrane receptors or intracellular transductors of mitogenic signals, thus limiting cell proliferation. Expression of this miRNA generally increases with cell differentiation whereas it is downregulated in several types of tumors, such as breast, lung, ovarian, gastric, colon, and cervical cancers, neuroblastoma, medulloblastoma, glioblastoma, and retinoblastoma. In this study, we focused on hepatocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…It has also been demonstrated that the deletion of mouse Mir122 resulted in hepatosteatosis, hepatitis, and the development of tumors resembling HCC[ 121 ], while its re-expression reduced disease manifestations and tumor incidence[ 122 ]. We recently reported a lower expression of miR-125a-5p in HCC tissues compared with non-tumor tissue in 55 patients with hepatocellular cancer of different etiologies[ 123 ]. In addition, we found a significant upregulation of three oncogenes in HCC tissue, MMP-11, c-Raf and Sirt-7, already validated as molecular targets of miR-125a-5p, an observation that provides an explanation for the tumor suppressor activity exerted by this microRNA.…”
Section: Micrornas As Biomarkers Of Hbv-related Liver Diseasesmentioning
confidence: 99%
“…It has also been demonstrated that the deletion of mouse Mir122 resulted in hepatosteatosis, hepatitis, and the development of tumors resembling HCC[ 121 ], while its re-expression reduced disease manifestations and tumor incidence[ 122 ]. We recently reported a lower expression of miR-125a-5p in HCC tissues compared with non-tumor tissue in 55 patients with hepatocellular cancer of different etiologies[ 123 ]. In addition, we found a significant upregulation of three oncogenes in HCC tissue, MMP-11, c-Raf and Sirt-7, already validated as molecular targets of miR-125a-5p, an observation that provides an explanation for the tumor suppressor activity exerted by this microRNA.…”
Section: Micrornas As Biomarkers Of Hbv-related Liver Diseasesmentioning
confidence: 99%
“…MircroRNA-125a-5p (miR-125a), denominated lin-4 in nematodes, is of special interest, since it is very well conserved in evolution 16 and plays a pivotal role in development and cell differentiation 1 , 17 20 . Expression of this miRNA generally increases with cell differentiation whereas it is downregulated in several types of tumors, including breast 21 23 , gastric 24 , cervical 25 , lung 26 , 27 , ovarian 28 , and colon 29 cancers, retinoblastoma 30 , medulloblastoma 31 , glioblastoma 32 , neuroblastoma 33 , and hepatocellular carcinoma 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…miR‐125a is an acknowledged miRNA for suppressor genes. It plays a tumor suppressing part in tumors such as gastric cancer and liver cancer .…”
Section: Discussionmentioning
confidence: 99%